Reminder on releasing payment upon R/B 017 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder to release payment against R/B 017 in order to assure the normal operation of BRACU new campus project.